Ethnoscience of Physics-Math: Calculation of Energy and Wages of Hoeing Farmers in Indonesia - Sabaruddin Chaniago (Postgraduate, University of Mataram, 2023)
The purpose of this study is to describe the analysis of farmers' economic concepts, especially the wage system of land hoe labourers. The low wage value of land hoe labourers is a deep concern considering the amount of energy expended by farmers in spending their potential throughout the day on the farm. In this context, the use of mathematical ethnoscience in human life is something that may not be clearly observed. This study becomes very interesting, when the awareness of local power to apply mathematical concepts is realised as an amplifier of human needs in solving their life problems. Life's problems are increasingly complicated in the construction of inevitable needs. This research method is a qualitative research method with a descriptive approach. This research operationally examines various sources of literature relevant to the above research context. This research is qualitative descriptive research using the content analysis method to obtain the results that in the use of hoes there are several physics concepts about mechanics including the concepts of force, rotational dynamics, work and energy. Based on the results of data analysis and discussion, it can be concluded that there are several physics concepts in the use of hoes in cultivating the soil starting from the mechanical advantages of using a hoe, the moment of force when swinging a hoe, the compressive force exerted by the hoe, the lifting force when lifting the soil, the pulling force when pulling the soil, and the effort and energy expended during hoeing activities.